Ice-volume-forced erosion of the Chinese Loess Plateau global Quaternary stratotype site - T. Stevens (Nature Portfolio, 2018)
A basic requirement for reconstructing past environmental change is accurate understanding of sediment age. Here, the authors show that the interpretation of a benchmark archive in China has been inaccurate, and that ice volume primarily controls desert dynamics, sediment preservation, and precipitation at the site.